COGNITIVE DOMAIN OF ENGLISH TEXTBOOK FOR GRADE 5 ELEMENTARY SCHOOL IN MALAYSIA - fadlilah nurul oktaviani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
One of the aspects that is implemented in the textbook is cognitive skill which deals with intellectual or thinking ability and guide the students to have knowledges and be active in the classroom. This paper focuses on identifying the type and most dominant cognitive domain reflected in textbook and aims to know the type and find out the most dominant cognitive domain. The type of this paper is qualitative research and the research design is descriptive qualitative. The subject is English textbook for five graders of elementary school entitled “English Year 5” which is published by Malaysia ministry of education with KSSR (Kurikulum Standard Sekolah Rendah) year 5 as the curriculum. The researcher analyzed the instructional activities based on the revised Bloom’s taxonomy by Anderson (2001). The result reveals that the total number of the instructional activities is 235. The type of cognitive domain is creating with 71, understanding is 55,  remembering shows 41, applying shows 34, analyzing shows 20 and the last domain is evaluating that has 14. Creating, the most cognitive domain shows that the authors want the students be able to put elements together to form a coherent or functional whole, that is reorganizing elements into a new pattern to communicate relate their ideas accurately means the authors facilitate students to create ideas in order to communicate to other people. The authors use communicative approach to write the textbook that its guides the teachers and students to become more active, communicative and collaborative in the class.